Motivation and satisfaction of visitors at the recreational area in Alor Lempah, Kuala Kubu Bharu, Selangor, Malaysia - Jaafar, Nur Jazilah; Abdul Aziz, Nor Akmar; Zainal Abidin, Zulkhairi Azizi; Lukhman, Arief Aiman (Faculty of Human Ecology, Universiti Putra Malaysia, 2024)
The sustainability of the recreational area is intricately linked to visitor satisfaction and the determinants affecting their likelihood of returning to the site. However, few information on this relationship has been researched. We investigated whether visitors are satisfied with their visit to Alor Lempah for recreation activity and to explore the factors influencing the visitor satisfaction by push and pull motivation. A face-to-face questionnaire was used to collect data from 400 visitors for three months. These included socio-demographic data, visit characteristics, factors influencing visitation, recreation area satisfaction and revisit intention to Alor Lempah. The multiple regression analysis was used to analyse the association between motivation and satisfaction level. Psychological and physiological factors and environmental factors were the primary factors motivating recreational area visitation. 95% of the visitors want to revisit Alor Lempah in the future. Long-distance visitors who lived more than 10km from Alor Lempah and visitors who came by car made up the majority of recreational area visitors. Interestingly, social and economic factors significantly impacted amenities/facilities satisfaction at Alor Lempah. Good spots for recreation or picnic areas and feeling safe were found to be major factors of user experience and environment satisfaction, while convenient changing rooms and inadequate number of trash bins limited the satisfaction level of amenities and facilities. These findings could be useful for recreation area planners in developing guidelines to improve visitor satisfaction and promote the sustainability of Alor Lempah.